Symptoms and Otorhinolaryngological Sequalae in Long Covid - Loli, Alessandra; Müller, João Victor Costa; de Azevedo, Eric Schneider; Martins, Regina Helena Garcia (International Archives of Otorhinolaryngology, 2025)
After the pandemic caused by the coronavirus, many patients have presented remaining otorhinolaryngological symptoms, but most of them are unknown to health professionals.To characterize otorhinolaryngological symptoms and sequelae in hospitalized patients for Covid-19.We made a recall to patients hospitalized between April 2020 and April 2022 due to Covid-19. Demographic data, initial and remaining symptoms, days of hospitalization, intubation and/or tracheostomy, and vaccination data were collected.845 patients were hospitalized, 441 died, 404 patients were contacted by telephone, but only 109 responded to the questionnaire about initial and remaining otorhinolaryngological symptoms after 1.5 to 2 years of illness, 59 men and 50 women, with an average age of 58.61 years (20 to 94). Two study groups were composed: G 1 (n- 44; with remaining symptoms) and G 2 (n- 65; without remaining symptoms). 81% of patients in G1 and 67% of patients in G2 had been hospitalized for up to 20 days. Intubation occurred in 17 patients (G1–7; G2–10). Seven patients underwent tracheostomy. The most prevalent initial and remaining otorhinolaryngological symptoms, respectively, were dyspnea (68.8%; 14.6%), cough (65.1%; 11.92%), nasal obstruction (47.7%; 5.58%), smell dysfunction (44%; 11%), taste dysfunction (42%; 4.58%). Vaccination was reported by 54 patients (G1–21; G2–34).Otorhinolaryngological symptoms were common in patients hospitalized for Covid-19, especially dyspnea, cough, nasal obstruction, smell, and taste dysfunction. Although there was a favorable long-term evolution, 40% of patients maintained permanent symptoms, such as smell and taste dysfunction and dizziness, unrelated to the vaccine doses.
Keywords: long covid; otorhinolaryngological sequelae; otorhinolaryngological symptoms